Щодо проблеми використання в Україні наукометричних показників: на прикладі аналізу публікаційної активності окремого науковця - Якимчик, А.І. (Вісник НАН України, 2020)
Статтю присвячено проблемі використання в Україні наукометричних показників для оцінювання результатів наукової діяльності на прикладі конкретного науковця — академіка НАН України В.І. Старостенка, який у цьому році відсвяткував свій 85-річний ювілей. Узагальнено науковий доробок цього видатного вченого-геофізика і організатора науки, наведено кількісні показники з його профілів у бібліографічних базах даних Scopus і Web of Science Core Collection. Проаналізовано повний перелік його наукових праць за останні 30 років і окремо розглянуто список публікацій у 2015–2019 рр. за даними наукометричної бази Scopus. Зроблено висновок, що зазначені бібліографічні реферативні бази даних орієнтуються насамперед на англомовні публікації, а статті та монографії іншими мовами (українською, російською) в них відображено некоректно і неадекватно. The purpose of this work is to investigate the problem of using scientometric indicators in Ukraine to evaluate the results of scientific activity using the example of a particular scientist. The paper dedicated to the 85th anniversary of the Academician of the NAS of Ukraine V.I. Starostenko summarizes scientific achievements of this outstanding scientist, geophysicist and organizer of science. In the author's opinion, the most important highlights of Starostenko's career are his professional achievements, publications, and his role in the training of highly qualified personnel in the field of geophysics. The article gives quantitative indicators from Scopus bibliographic database profiles and Web of Science Core Collection. Scientific publications for over the last thirty years, and then in more detail from 2015 to 2019, are listed and analyzed in short form according to the Scopus science database. A comparison of the number of scientific articles with the earlier stage of scientific career is made. The paper argues that the publication activity of the scientist in question has not decreased with age; he publishes about 10 scientific articles a year. However, only three of them are indexed in Scopus and four in WoS. The author explains this by the fact that these bibliographic reference databases are focused primarily on English-language publications, and generally articles and monographs in other languages (Ukrainian and Russian) are not correctly and adequately indexed. Particular attention is paid to the work of this scientist as a reviewer and editor- in-chief of the scientific monthly “Geophysical Journal”.